2017
DOI: 10.1016/j.tig.2017.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Clocks and Metabolism: Implications for Microbiome and Aging

Abstract: The circadian clock directs many aspects of metabolism to separate in time opposing metabolic pathways and optimize metabolic efficiency. The master circadian clock of the suprachiasmatic nucleus synchronizes to light, while environmental cues such as temperature and feeding out of phase to the light schedule may synchronize peripheral clocks. This misalignment of central and peripheral clocks may be involved in the development of disease and the acceleration of aging, possibly in a gender specific manner. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 91 publications
0
47
0
1
Order By: Relevance
“…SNPs with the highest LOD in the QTL regions for Mollicutes and Bacteroidales were found to lie within genes Insig2 and Ksr2 respectively. Insig2 encodes a transmembrane protein that releases SREBP proteins to the endoplasmic reticulum where they exert control over lipid metabolism [Paschos et al 2017]. Relationships between gut microbiome and lipid metabolism have already been established [Velagapudi et al 2010, Li et al 2008, and our reported association between Mollicutes and Insig2 further suggest some kind of interaction between Mollicutes abundance and lipid metabolism.…”
Section: Discussionmentioning
confidence: 54%
“…SNPs with the highest LOD in the QTL regions for Mollicutes and Bacteroidales were found to lie within genes Insig2 and Ksr2 respectively. Insig2 encodes a transmembrane protein that releases SREBP proteins to the endoplasmic reticulum where they exert control over lipid metabolism [Paschos et al 2017]. Relationships between gut microbiome and lipid metabolism have already been established [Velagapudi et al 2010, Li et al 2008, and our reported association between Mollicutes and Insig2 further suggest some kind of interaction between Mollicutes abundance and lipid metabolism.…”
Section: Discussionmentioning
confidence: 54%
“…Expanding the role of circadian diurnal rhythmicity to physiological and disease conditions The diurnally changing microbiome and its impact on the host may influence other microbiome-associated physiological states and diseases. For example, aging is associated with distinct changes in the gut microbiome [69,[185][186][187][188][189][190][191][192][193][194][195][196][197][198][199][200][201][202][203][204]. Moreover, the microbiome has been implicated to modulate various aspects of aging including longevity [205], and very old individuals were found to feature a microbiota composition enriched for "health-promoting" commensals [206].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Moreover, the microbiome has been implicated to modulate various aspects of aging including longevity [205], and very old individuals were found to feature a microbiota composition enriched for "health-promoting" commensals [206]. While the microbiota is relatively stable in adulthood [72], the aging process is associated with a change in an individual's microbiome composition, which is thought to be mainly driven by environmental effects such as the use of antibiotics, changes in nutrition, and the development of chronic illnesses, including metabolic syndrome and inflammatory diseases [73,[185][186][187][188][189][190][191][192][193][194][195][196][197][198][199][200][201][202][203][204]. The microbial diversity decreases significantly with age [207], while the inter-individual variability in microbiota increases significantly in elderly compared to younger adults [208].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…3 Another study also mentioned that disruption of microbiota interferes our normal circadian clock, consequently provoking metabolic disorders accompanied by exaggerating the ageing. 4,5 In mammals, the change in diversity of gut microbiota has been linked to the different age groups. In general, elderly peoples result less Bacteroidetes in terms of quantity and quality and more Firmicutes compared with healthy middle-aged people In southwest China cohort.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…The molecular events underlying are commensal bacteria secreted short‐chain fatty acids to regulate the hormone for skeletal growth namely insulin‐like growth factor‐1 . Another study also mentioned that disruption of microbiota interferes our normal circadian clock, consequently provoking metabolic disorders accompanied by exaggerating the ageing . In mammals, the change in diversity of gut microbiota has been linked to the different age groups.…”
Section: Introductionmentioning
confidence: 99%